Assessment of the current practice of psychiatric pharmacists in the United States - Silvia, Richard J. (Ment Health Clin, 2020)
INTRODUCTION: A comprehensive review of psychiatric pharmacy practice has never been performed in the United States. As psychiatric pharmacists become more involved in mental illness treatment, determining the current state of practice is important to help advance the specialty. The Professional Affairs Committee of the College of Psychiatric and Neurologic Pharmacists (CPNP) was charged with performing this review to define current psychiatric pharmacy practice. METHODS: An electronic survey was sent to all pharmacist members of CPNP and all nonmember Board Certified Psychiatric Pharmacists (BCPPs) in the United States in late summer 2019. The survey consisted of 36 questions across multiple domains to obtain information about respondents' education and training background, practice setting and type, and information about prescriptive authority and other areas. An initial e-mail invitation was sent along with 2 reminder e-mails over the subsequent 2 weeks. RESULTS: A total of 334 of 1015 pharmacists completed the survey (32.9%). Responders completed a postgraduate residency 77.8% of the time, and 88.3% were BCPP. Practice settings were split evenly between inpatient and outpatient practices or a combination of the 2. Among respondents, 46.5% reported having prescriptive authority as part of their practice, and 41.3% reported treating nonpsychiatric as well as psychiatric illnesses. Prescriptive authority was more likely in outpatient practices and in those treating nonpsychiatric illnesses. DISCUSSION: The current practice of psychiatric pharmacy is incredibly varied in terms of practice setting, activities performed, and services provided. Further exploration is needed to help determine the optimal role of psychiatric pharmacists.